A novel fault line selection method based on empirical mode decomposition and differential spectrum - ZHENG Chen; WANG Xiao-wei; LIU Ya-juan; TIAN Shu (Gong-kuang zidonghua, 2013)
The paper proposed a novel single-phase grounding fault line selection method of small current grounding system based on EMD and differential spectrum. The method uses EMD method to decompose transient zero-sequence current and extract high-frequency IMF1 component of each line, obtained differential spectrum and fluctuation value of IMF1 component of each line according to definitions of differential spectrum and fluctuation value, and found out the fault line which has the maximum fluctuation value of IMF1 component by comparing fluctuation values of IMF1 component of each line. The experiment results showed that the method has higher accuracy of line selection and is suitable for fault line selection of small current grounding system under different grounding resistances and different fault initial phase angles.